Application of MUSIC Algorithm for Object Localization Without Diagonal Elements of Multi-Static Response Matrix (Communications in Computational Physics, 2025)
Generally, to apply the MUltiple SIgnal Classification (MUSIC) algorithmfor the rapid imaging of small objects, complete elements of the multi-static response(MSR) matrix must be collected. However, in some real-world applications in microwave imaging, diagonal elements of the MSR matrix are unknown. Nevertheless, itis possible to obtain imaging results using a traditional approach but theoretical reasonof the applicability has not been investigated yet. In this paper, we consider the application of MUSIC for a fast identification of small objects from collected MSR matrixin both transverse magnetic (TM) and transverse electric (TE) polarizations. In orderto examine the applicability, fundamental limitation, and various properties of MUSIC, we establish mathematical structure of the three imaging functions and explorethat the main factors of the imaging functions are Bessel function of order zero, one,and two. The established structures demonstrate why the existence and location ofsmall objects can be retrieved via MUSIC without the diagonal elements of the MSRmatrix. Results of numerical simulations with noise-corrupted synthetic data are alsoprovided to support the identified structures.
Keywords: MUltiple SIgnal Classification (MUSIC); multi-static response (MSR) matrix; Bessel functions; numerical simulations.